Event Marketing As The Instrument For Promotion Of Territorial Brands (On The Example Of The Republic Of Tatarstan And The Republic Of Udmurita) - A. Nikitin, Aleksey (2018)
In recent decades, there has been seen a rapid growth in the tourism industry represented in the number of destinations available to tourists. This is due to the active growth and development of world tourism. Despite the positive trend, there is a loss of individuality and identity of the territories. In other words, a tourist destination becomes easily replaceable. To prevent this, an integrated promotion of territories is necessary. So, one of the integrated tools is the event marketing. Events deserve the most attention when developing a campaign to promote locations, since a widely promoted event itself becomes a brand, which allows it to be widely used in the construction of a further location strategy. In the paper there is a conclusion that when developing event promotion of locations it is necessary to rely on the cultural identity of the territory.